Penerapan Program Unggulan Sebagai Bentuk Dedikasi Peserta Didik Terhadap Sekolah - Ahmad Fauzi Al Firdaus; Siti Fatimah; Magda Aprilina (Universitas Negeri Malang, 2023)
Abstract: The relationship between the school and the community is a relationship between the school and thecommunity that starts from knowing each other, understanding each other, helping each other.Public relations activities applied in educational institutions use several techniques in the process bylooking at the situation or conditions of the surrounding environment. Thisresearch aims todetermine (1) public relations management planning, (2) implementation of public relationsmanagement, (3) evaluation of public relations management carried out by MAN 1 Malang City. Thisstudy used a qualitative approach, data collection techniques in this study through interviews,observation, and analysis of literature studies. Data analysis was carried out by combining thefindings of interviews supported by literature reviews of articles relevant to the topic of discussion.The results showed that public relations management in MAN 1 Malang City can be said to besuccessful, as evidenced by the increase in achievement achieved by students. The public relationsmanagement process in MAN 1 Malang City through planning involving the principal, public relationswaka, madrasah committee, and teacher council. The implementation of public relationsmanagement is carried out by publishing a magazine every one school year. Evaluation of publicrelations management is carried out in stages by preparing documents and seeing the resultingimpact.Keywords: School, Community, EducationAbstrak: Hubungan sekolah dengan masyarakat merupakan suatu hubungan antara sekolah denganmasyarakat yang berawal dari saling mengenal satu sama lain, saling memahami, saling menolong.Kegiatan humas yang diterapkan di lembaga pendidikan menggunakan beberapa teknik dalamprosesnya dengan melihat situasi atau kondisi dari lingkungan sekitar. Penelitian ini bertujuan untukmengetahui (1) perencanaan manajemen humas, (2) pelaksanaan manajemen humas, (3) evaluasimanajemen humas yang dilakukan oleh MAN 1 Kota Malang. Penelitian ini menggunakan pendekatankualitatif, teknik pengumpulan data dalam penelitian ini melalui wawancara, observasi, dan analisisstudi literatur. Analisis data dilakukan dengan memadukan temuan hasil wawancara didukung dengan kajian literatur dari artikel-artikel yang relevan dengan topik bahasan. Hasil penelitian menunjukan bahwa manajemen humas di MAN 1 Kota Malang dapat dikatakan berhasil, terbuktidengan adanya peningkatan prestasi yang diraih oleh peserta didik. Proses manajemen humas diMAN 1 Kota Malang melalui perencanaan dengan melibatkan kepala sekolah, waka humas, komitemadrasah, dan dewan guru. Pelaksanaan manajemen humas dilakukan dengan menerbitkan majalahsetiap satu tahun pelajaran. Evaluasi manajemen humas dilakukan secara bertahap denganmempersiapkan dokumen serta melihat dampak yang dihasilkan.Kata kunci: Sekolah, Masyarakat, Pendidikan